Evaluation of Wheat Genotypes in Far Western Hills of Nepal - Prasai, Hari Kumar; Shrestha, Jiban (International Journal of Applied Sciences and Biotechnology, 2015)
Coordinated Varietal Trial (CVT) and Advanced Varietal Trial (AVT) of wheat were conducted at Regional Agricultural Research Station, Doti during the year 2012 and 2013. Microplot Yield Trial (MPYT) were conducted during the year 2013. Total 20 genotypes were included in CVT experiment of both years. Although the difference in grain yield due to genotypes was not found significant during the year 2012, NL 1144 recorded the highest grain yield (4309 kg/ha) followed by NL 1140 (4295 kg/ha) and NL 1147 (4165 kg/ha) respectively. But in the year 2013, NL 1097 produced the highest grain yield (4641 kg/ha) followed by NL 1135 (4383 kg/ha) and NL 1164 (4283 kg/ha) respectively. Statistically, the difference in grain yield due to genotypes was not found significant in the year 2013. Combined analysis over years was also carried out. Out of 20, only 10 genotypes were included in the CVT experiment, which were found similar in both years. Genotypes NL 1097 (4079 kg/ha), NL 1140 (3814 kg/ha) and NL 1093 (3773 kg/ha) were found high yielding genotypes for river basin agro-environment of far western hills. Statistically, effect of year in tested characters was found significant whereas treatment effect was observed non-significant. Similarly, 20 genotypes of wheat were included in AVT of wheat during the year 2012 and 2013. Out of the genotypes included in AVT during the year 2012, KISKADEE No.1recorded the highest grain yield (3824 kg/ha) followed by CHEWINK No. 1 (3643 kg/ha) and WK 2120 (3583 kg/ha). Statistically all the tested characters except grain yield were found significantly different due to genotypes. But in the same experiment of the year 2013, WK 2412 genotype recorded the highest grain yield (4407 kg/ha) followed by WK 2411 (4329 kg/ha) and Munal-1 (4054 kg/ha). Statistically the difference in grain yield and other tested characters were found significantly different. Due to dissimilarity in the tested genotypes we could not carry-out the combined analysis over years. Total 30 genotypes were included in the MPYT experiment of the year 2013. Genotype WK 2272 recorded the highest grain yield (6080 kg/ha) followed by the genotypes WK 2274 (5152 kg/ha) and WK 2278 (4480 kg/ha) respectively. Statistically, the difference in grain yield and other tested characters were found significantly different due to genotypes. Int J Appl Sci Biotechnol, Vol 3(3): 417-422